The impact of profitability, leverage, managerial ownership, and dividend payout ratio on income smoothing - Suwaldiman Suwaldiman; Rifda Nafiesah Lubis (Jurnal Akuntansi dan Auditing Indonesia, 2023)
This paper examined the impact of profitability, leverage, management ownership, and dividend payout ratio on income smoothing of companies listed in IDX in the range of 2015-2020 based on Eckel Index. The lower the Eckel Index the higher the intensity of income smoothing and vice versa. The hypothesis proposed were tested by a multiple regression analysis. This research concluded that return on asset, debt to capital ratio, and dividend payout ratio have significant and positive impacts on the Eckel Index. It is interpreted that the higher these variables, the lower the intensity of income smoothing. However, this research revealed that management ownership has a negative and significant impact on the Eckel Index, thus proving that managers ownership will drive them to conduct the income smoothing.